Vitamin D, Metals and Preterm Birth - Fisher, Mandy (Université d'Ottawa / University of Ottawa, 2023)
Background: Environmental chemicals may interrupt physiological adaptations necessary in pregnancy, contributing to pregnancy complications with health implications for the mother and child. Nutrients may modify the impact of chemical exposures by blocking their absorption or facilitating their excretion. However, the nature, directionality, and implications of these relationships remain unclear. Objectives: We sought to understand: 1) the potential bidirectional nature of the relationship between vitamin D (25-hydroxyvitamin D, 25OHD) and the toxic metals cadmium (Cd) and lead (Pb) in pregnancy; 2) the association between metals (Cd, Pb, arsenic (As), mercury) and preterm birth and the potential modification of that association by 25OHD; and 3) the long-term association of pregnancy complications with maternal cardiometabolic health. Methods: We used data from the Maternal-Infant Research on Environmental Chemicals Study (n=1983) pregnancy cohort, including long-term follow-up approximately 9 years post-pregnancy. We used cross-lagged panel models to determine the direction of the relationship of 25OHD with Cd and Pb in pregnancy, discrete-time survival analysis to examine the association between metals in pregnancy and preterm birth, and multivariable linear regression to investigate the association of pregnancy complications with long-term maternal outcomes. Results: Each doubling in first trimester 25OHD concentrations was associated with 9% (95% CI: -15%, -3%) lower 3rd trimester Cd and 3% (-7, 0.1%) lower Pb. One-unit increases in Pb (μg/dL) and arsenic (μg/L) concentrations in pregnancy were associated with an increased relative risk (RR) of preterm birth (RR_Pb: 1.48, 95% CI: 1.00, 2.20; RR_As: 1.10, 95% CI 1.02, 1.19); the association with Pb was stronger among those with lower 25OHD. Finally, relative to uncomplicated pregnancy, experiencing a pregnancy complication was positively associated with body fat percentage (β=2.6, 95% CI: 0.3, 4.8) and systolic (average increase of 9.0 mm Hg, 95% CI 5.1, 12.8) and diastolic (average increase of 5.5 mm Hg, 95% CI: 2.6, 8.4) blood pressure 9 years later. Conclusions: Nutrient status during pregnancy may affect and interact with environmental chemicals to impact pregnancy outcomes. Future studies should continue to use methods that elucidate the causal direction of associations and evaluate interactions. Chemicals associated with pregnancy complications could have lasting impacts on maternal health.
Keywords: vitamin D; preterm birth; Cardiometabolic; Metals